Profile of nursing consultations to hematological patients in a blood center in Northern Brazil (Research, Society and Development, 2021)
Construction of a care profile aimed at describing the role of nurses in the Nursing Consultation (CE) to hematological patients. This study has a quantitative-descriptive character, carried out in a regional blood center in the municipality of Castanhal, located in the State of Pará. For data collection, an analysis of the standard operating protocols was performed, verifying the nursing records and the survey of the records monthly production of nursing consultations, from June to November 2020. The variables were analyzed: number of patients registered by diagnosis; distribution by age group and sex; types of hematological diseases; type of EC (1st time, return and reception); conducts in EC outcomes; And CE to hemophiliacs. Regarding the patients registered at the blood center, there is a predominance of sickle cell disease (56.5%) and hemophilia A (31.8%), in the age group of 0 to 10 years, in the male gender. As for FB in hematological diseases (n = 78), there was a predominance of sickle cell disease (51.2%) and hemophilia A (29.4%), with a greater number of consultations for the first time, which were referred to the Hematological Care Priority. Secondary prophylaxis prevailed in EC for hemophiliacs. Nurses play a fundamental role in caring for patients with hematological diseases and need to be adequately prepared to perform this responsibility, seeking to reduce the distances between practice and available scientific knowledge, in order to offer systematic care and, consequently, to quality.